Non-rhabdomyosarcoma soft-tissue sarcomas in children: Contemporary appraisal and experience from a single centre - Sajid S Qureshi; Monica Bhagat (Wolters Kluwer Medknow Publications, 2015)
Nonrhabdmyosarcoma soft tissue sarcomas (NRSTS) include a cluster of different types of soft tissue sarcomas clubbed together due to the rarity of individual subtypes. The diagnostic accuracy is lately reinforced due to the availability of immunohistochemical and molecular markers. Surgery is the central modality of treatment since many of them are insensitive to chemotherapy. With the availability of rational risk stratification system, efforts are in progress to evaluate the role of neoadjuvant chemotherapy and radiotherapy to improve outcomes especially for the locally advanced disease. The survival remains dismal for metastatic disease. This review highlights the current status of NRSTS and also describes the experience from a single centre in treatment of NRSTS.